Emergency online learning during the first Covid-19 period: students’ perspectives from Bosnia and Herzegovina, North Macedonia, Poland and Turkey - Miloshevska Lina; Gajek Elżbieta; Džanić Nihada Delibegović; Hatipoğlu Çiler (ExELL (Explorations in English Language and Linguistics))
In spring 2020 both teachers and learners experienced the interruption of education as it had been established for over 150 years and seemed to be unchangeable. The paper focuses on students’ perspectives on how they perceive the changes in learning due to the pandemic educational emergency response based on the results of a survey of students in four countries: Bosnia and Herzegovina, North Macedonia, Poland and Turkey. We aim at discussing the data collected at the end of the 2019-2020 Spring semester. The research focuses on the accessibility of the tools for learning, modes of instruction, as well as interaction patterns. In addition, we present students’ opinions on the difficulties they experienced, the learning strategies they adopted and what aspects of online learning should remain as a regular educational practice after the pandemic period.